Analysis of Viral and Cellular Factors Influencing Herpesvirus-Induced Nuclear Envelope Breakdown - Grimm, Katharina S. (American Society for Microbiology, 2012)
Herpesvirus nucleocapsids are translocated from their assembly site in the nucleus to the cytosol by acquisition of a primary envelope at the inner nuclear membrane which subsequently fuses with the outer nuclear membrane. This transport through the nuclear envelope requires homologs of the conserved herpesviral pUL31 and pUL34 proteins which form the nuclear egress complex (NEC). In its absence, 1,000-fold less virus progeny is produced. We isolated a UL34-negative mutant of the alphaherpesvirus pseudorabies virus (PrV), PrV-ΔUL34Pass, which regained replication competence after serial passages in cell culture by inducing nuclear envelope breakdown (NEBD) (B. G. Klupp, H. Granzow, and T. C. Mettenleiter, J. Virol. 85:8285–8292, 2011). To test whether this phenotype is unique, passaging experiments were repeated with a UL31 deletion mutant. After 60 passages, the resulting PrV-ΔUL31Pass replicated similarly to wild-type PrV. Ultrastructural analyses confirmed escape from the nucleus via NEBD, indicating an inherent genetic disposition in herpesviruses. To identify the mutated viral genes responsible for this phenotype, the genome of PrV-ΔUL34Pass was sequenced and compared to the genomes of parental PrV-Ka and PrV-ΔUL34. Targeted sequencing of PrV-ΔUL31Pass disclosed congruent mutations comprising genes encoding tegument proteins (pUL49, pUL46, pUL21, pUS2), envelope proteins (gI, pUS9), and protease pUL26. To investigate involvement of cellular pathways, different inhibitors of cellular kinases were tested. While induction of apoptosis or inhibition of caspases had no specific effect on the passaged mutants, roscovitine, a cyclin-dependent kinase inhibitor, and U0126, an inhibitor of MEK1/2, specifically impaired replication of the passaged mutants, indicating involvement of mitosis-related processes in herpesvirus-induced NEBD.